cropping systems in the subhumid zone of Nigera: A review - Tening, A.S.; Tarawali, G.; Adeoye, K.B.; Mohamed-Saleem, M.A.; Omueti, J.A.I. (International Livestock Centre for Africa, 1994)
During the 1980s the management and nutrient requirements of Stylosanthes in pastures and cropping systems were investigated at several ILCA research sites in northern Nigeria. While Stylosanthes guianensis cv Cook and cv Schofield responded to phosphorus (P), Stylosanthes hamata cv Verano did so to a lesser extent. Results from nutrient omission trials showed that the soils of one specific experimental area were deficient in most of the essential nutrients. Application of Kanwa (a local mineral salt) of up to 100 kg/ha on old and newly established Verano stylo increased dry mater (DM) yield significantly. Good growth of Stylosanthes capitata was associated with low pH and calcium, but high levels of organic carbon and total nitrogen (N) in the top soil. On sites with indurated or poorly drained subsoils, disc-harrowing followed by sub-soiling lowered bulk density and increased water storage as compared to ridging or no second tillage; it also resulted in a higher DM yield of Verano stylo.